Mineralocorticoid receptor antagonists eplerenone and spironolactone modify adrenal cortex morphology and physiology - Pereira, SS (2021)
Mineralocorticoid receptor antagonists (MRAs) are a class of anti-hypertensive drugs that act by blocking aldosterone action. The aim of this study was to evaluate whether the MRAs spironolactone and eplerenone influence adrenal cortical physiology and morphology. Spontaneous hypertensive rats (SHR, n = 18) and normotensive rats (WKY, n = 18) were randomly exposed to a daily dose of spironolactone (n = 6), eplerenone (n = 6), or no drug (n = 6) over 28 days. After that, aldosterone, corticosterone, and 11-deoxycorticosterone plasma concentrations were quantified. Adrenal glands were subjected to morphological analysis to assess lipid droplets content, capsular width, cell proliferation, and steroidogenic proteins expression. The adrenal cortex in untreated SHR showed higher lipid droplet content as than in WKY. In SHR, MRA treatment was associated with higher circulating aldosterone levels and Ki-67 expression in aldosterone-secreting cells. In WKY, the only difference observed after MRA spironolactone treatment was a narrower capsule. There was no difference in abundance of steroidogenic enzyme between groups. In conclusion, MRAs modify adrenal gland function and morphology in SHR. The effects observed within the adrenal glomerulosa with aldosterone-secreting cell proliferation and higher circulating aldosterone levels suggests that MRA treatment provokes activation of the renin angiotensin system. The prognostic value of hyperaldosteronism secondary to MRAs blockade requires further investigation.